2008
DOI: 10.1007/s10545-008-0752-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced carbohydrate intake in citrin‐deficient subjects

Abstract: Citrin is the liver-type aspartate-glutamate carrier that resides within the inner mitochondrial membrane. Citrin deficiency (due to homozygous or compound heterozygous mutations in the gene SLC25A13) causes both adult-onset type II citrullinaemia (CTLN2) and neonatal intrahepatic cholestasis (NICCD). Clinically, CTLN2 is characterized by hyperammonaemia and citrullinaemia, whereas NICCD has a much more varied and transient presentation that can include multiple aminoacidaemias, hypoproteinaemia, galactosaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…A recent study has disclosed that carbohydrate intake was selectively reduced in the diet of most citrin-deficient subjects, compared to that of the general Japanese population (6). While the PFC ratio of the general Japanese population was 14 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 A 7 0 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has disclosed that carbohydrate intake was selectively reduced in the diet of most citrin-deficient subjects, compared to that of the general Japanese population (6). While the PFC ratio of the general Japanese population was 14 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 Fp1 Fp2 F3 F4 C3 C4 P3 P4 O1 O2 F7 F8 T3 T4 T5 T6 A 7 0 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that carbohydrate intake was selectively reduced in the diet of most subjects with CD, compared with that of the general population. 19,20 Whereas the protein/ fat/carbohydrate ratio of the general Japanese population is 14% to 15%, 25% to 30%, and 54% to 58%, respectively, that of the CD subjects is 19% 6 2%, 44% 6 5%, and 37% 6 7%, respectively. 19 This carbohydrate aversion in CD is unique in contrast to the protein aversion in other urea cycle enzyme deficiencies and is assumed to be directly linked to CD.…”
Section: Figurementioning
confidence: 98%
“…19,20 Whereas the protein/ fat/carbohydrate ratio of the general Japanese population is 14% to 15%, 25% to 30%, and 54% to 58%, respectively, that of the CD subjects is 19% 6 2%, 44% 6 5%, and 37% 6 7%, respectively. 19 This carbohydrate aversion in CD is unique in contrast to the protein aversion in other urea cycle enzyme deficiencies and is assumed to be directly linked to CD. 3 Lee et al reported 2 teenage CD siblings with FTT, which started after dietary change to a low-fat or a lowprotein diet to control dyslipidemia or hyperammonemia.…”
Section: Figurementioning
confidence: 98%
“…However, some patients suffer from various manifestations during the so-called apparently healthy period; some children are diagnosed with citrin deficiency without an apparent history of NICCD. The most striking symptom during the apparently healthy period is a peculiar preference for protein-and fat-rich food with an aversion to carbohydrate-rich food (Saheki et al 2008). Ketotic hypoglycemia is also relatively common during this period (Kure et al unpublished observation).…”
Section: Introductionmentioning
confidence: 99%